Microbial-derived peptidases are altered in celiac disease, non-celiac gluten sensitivity, and functional dyspepsia: a systematic review and re-analysis of the duodenal microbiome - Jennifer C. Pryor; Cheenie Nieva; Nicholas J. Talley; Guy D. Eslick; Kerith Duncanson; Grace L. Burns; Emily C. Hoedt; Simon Keely (Gut Microbes)
Dietary gluten triggers symptoms in patients with gluten-related disorders (GRDs) including celiac disease (CeD), non-celiac gluten sensitivity (NCGS), and subsets of patients with functional dyspepsia (FD). The gastrointestinal microbiota is altered in these patients when compared to healthy individuals. As the microbiota is crucial for the hydrolysis of gluten, we hypothesized that the capacity of the microbiota to digest gluten is reduced in these conditions. We systematically reviewed and re-analyzed published datasets to compare gastrointestinal microbiomes of GRD patients and identify signals explaining gluten responses. A systematic search of five databases was conducted to identify studies where the microbiota of CeD, NCGS, or FD patients was analyzed by 16S rRNA amplicon or shotgun metagenomic sequencing and compared to control populations. Where available, raw duodenal microbiota sequence data were re-analyzed with a consistent bioinformatic pipeline. Thirty articles met the inclusion criteria for this systematic review. Microbiota diversity metrics were not impacted by the diseases; however, genera including Streptococcus, Neisseria, and Lactobacillus were commonly altered in GRD patients. Re-analysis of duodenal 16S rRNA data was possible for five included articles but did not identify any consistent differentially abundant taxa. Predicted functional analysis of the microbiome revealed that peptidases including aminopeptidase, proline iminopeptidase, and Xaa-Pro dipeptidase are altered in CeD, NCGS, and FD, respectively. These microbial-derived peptidases hydrolyze bonds in proline-rich gluten peptides. While the gastrointestinal microbiota in patients with GRDs differ from controls, no distinct phenotype links them. However, alterations to the predicted functional capacity of the microbiome to produce gluten-hydrolyzing enzymes suggest that inappropriate digestion of gluten by the microbiome impacts host responses to dietary gluten in these conditions. These findings have implications for therapeutic management of GRDs, as treatment with gluten-degrading enzymes or tailored probiotics could improve disease outcomes by enhancing gluten digestion into non-reactive peptides.